2014
DOI: 10.1162/jocn_a_00618
|View full text |Cite
|
Sign up to set email alerts
|

ERPs Recorded during Early Second Language Exposure Predict Syntactic Learning

Abstract: Millions of adults worldwide are faced with the task of learning a second language (L2). Understanding the neural mechanisms that support this learning process is an important area of scientific inquiry. However, most previous studies on the neural mechanisms underlying L2 acquisition have focused on characterizing the results of learning, relying upon end-state outcome measures in which learning is assessed after it has occurred, rather than on the learning process itself. In the present study, we adopted a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
(123 reference statements)
1
11
1
Order By: Relevance
“…The importance of selective attention in L2 learning has been previously shown. In a previous ERP study, Batterink and Neville (2014) showed that L2 learners who spontaneously direct greater attention to open class words rather than closed class words when processing L2 input gain better syntactic learning. In eye-tracking studies on Japanese learners of English, participants who paid more attention to the task-relevant contents showed better task performance, although most participants did not read selectively Atkins, 2018, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The importance of selective attention in L2 learning has been previously shown. In a previous ERP study, Batterink and Neville (2014) showed that L2 learners who spontaneously direct greater attention to open class words rather than closed class words when processing L2 input gain better syntactic learning. In eye-tracking studies on Japanese learners of English, participants who paid more attention to the task-relevant contents showed better task performance, although most participants did not read selectively Atkins, 2018, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…There is ample evidence to suggest that it is precisely selective attention that is one of the key skills enhanced in bilinguals as compared to monolinguals (Bialystok 2009), and that it constitutes a significant predictor for L2 acquisition in adulthood (Batterink & Neville 2014, Issa & Morgan-Short, 2018). L2 learners acquire a new language based on the input they read or hear, but some features of the input become output only at very late stages of L2 acquisition, and some forms even fail to become intake altogether.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…To the author's knowledge, only two meaningful ALS neural studies have examined L2 grammar Bilingualism: Language and Cognition online. Batterink and Neville (2014) examined electrophysiological data that were recorded during training in the miniature French study (Batterink & Neville, 2013). Processing during training was analyzed in regard to ERP effects tied to selective attention (N100) and to successful identification of words (N400).…”
Section: L2 Online Learning Mechanismsmentioning
confidence: 99%